2004
DOI: 10.1258/002221504322928008
|View full text |Cite
|
Sign up to set email alerts
|

Survey of current undergraduate otolaryngology training in the United Kingdom

Abstract: The General Medical Council's core curriculum model for undergraduate medical training is leading to changes in the way specialist subjects are taught. A postal survey was undertaken to evaluate the current state of undergraduate clinical teaching in otolaryngology in the United Kingdom. Data were received from all 27 medical schools. Six medical schools (22 per cent) do not have a compulsory ENT attachment, although three of these offer an optional attachment. Fifty-eight per cent of all ENT attachments are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 2 publications
3
79
0
2
Order By: Relevance
“…Studies report that 10-25% of adult and up to 50% of paediatric consultations in General Practice relate to Otolaryngology topics (2,(7)(8)(9). Otolaryngology therefore forms an important part of the education of General Practitioners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies report that 10-25% of adult and up to 50% of paediatric consultations in General Practice relate to Otolaryngology topics (2,(7)(8)(9). Otolaryngology therefore forms an important part of the education of General Practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…A review, published in 1990, concluded that there had been few changes to undergraduate Otolaryngology since this address (11). Subsequent surveys have shown that 22-30% of UK medical schools do not provide a compulsory placement in Otolaryngology (1,2). This would suggest that a large proportion of medical students do not gain any experience in Otolaryngology.…”
Section: Introductionmentioning
confidence: 99%
“…However, a 2004 study in the UK found that only 78% of medical schools had a compulsory ENT attachment, and the average length of time spent in ENT was a week and a half 7 . Both the proportion of medical schools offering undergraduate ENT and the duration of attachment appears to have reduced recently 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It consisted of eight questions regarding exposure of undergraduates to the field of renal transplantation. (Figure 1) Although not validated, it was based upon a questionnaire from a similar study in the field of ENT [7]. Non-responders were sent a further copy of the questionnaire after four weeks, which were followed with a telephone call after a further four weeks, if necessary.…”
Section: Methodsmentioning
confidence: 99%